1364 Making training SIMple: the impact of a dedicated simulation fellow on the structure and delivery of simulation training in the St Richard's Hospital Paediatric Department. (17th August 2022) - Carter, Benjamin; Milton, Joanne
Abstract : Aims: Simulation training is enshrined by the Royal College of Paediatrics & Child Health (RCPCH) as an essential component of training and education in paediatrics. The St Richard's Hospital (SRH) simulation training programme has historically been delivered with variable consistency and uptake; and recent GMC feedback regarding local teaching had been poor. A new hybrid middle grade simulation fellow post was created with the following objectives: To formalise delivery of simulation training using educational theory, through regular scheduling within a weekly topic theme. To incorporate simulation debriefing as an essential component of simulation and enshrine a safe learning culture. To build a sustainable programme for delivery after the initial fixed term of the post. To evaluate the reception of this new programme and the satisfaction with simulation training at St Richard's Hospital Methods: An informal stakeholder needs assessment was performed to assess the existing structure of simulation teaching at SRH and to identify the essential curriculum items common to the RCPCH and GP training curricula and library of scenarios mapped to 20 curriculum items was created. Sessions were delivered weekly with a mixture of formats (in situ, sim-lab, A&E) with interdisciplinary inclusion (nursing/A&E/anaesthetics) wherever staffing allowed. Other thematically congruent educational activities, took place in each week, aiming to utilise a constructivist approach to teaching each curriculum theme, drawing on Bloom's Taxonomy (1) & Spiral Curriculum (2) Weekly simulation sessions were delivered, Debriefing was mandated within each session to allow for reflective practice and psychological safety. Quantitative and qualitative feedback was gathered after each session and an overall assessment of the teaching programme at the end of the academic year. Results: All participants who provided feedback rated both the simulation sessions and the debrief as 'useful' or 'very useful'. Themes of improved confidence, psychological safety, enjoyment and positive reception of interdisciplinary learning were identified in the feedback. Trainees and nursing staff remarked upon a positive change of attitude toward simulation as a result of the new style of delivery and debriefing. Differences in preferred scenario structure were identified between trainee types (Foundation/GPST/paediatric), pertaining to the types of scenarios offered (e.g. ward based vs A&E). The post itself was rated highly positively as a means of developing educational and leadership skills and was recommended as an out of programme post to diversify a trainee's portfolio. Conclusion: The presence of a simulation fellow with dedicated time for sim activity was essential to establish the new system within the department. Feedback suggested a reinvigoration of enthusiasm for simulation and sound educational value in sessions. The post was dually beneficial for both the departmental team training, and for the personal professional development of the individual in the role. Together, this has allowed for the embedding of essential infrastructure and ethos to ensure quality and sustainability in local simulation teaching moving forwards.